2019
DOI: 10.1111/1365-2478.12743
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of sands, Part 2: Implementation of contact‐based model to determine the elasticity of the grains from ultrasonic measurements

Abstract: The prediction of effective elastic properties of a granular medium using ultrasonic data based on contact models has been studied widely in both laboratory experiments and numerical simulations. In contrast, a calculation of the elastic properties of the constituent grains using similar data by inverting the equations from those models is a rather new concept. To do so, we have developed a controlled experiment technique that includes a uniaxial compaction test and measures ultrasonic velocities of four uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Journal of Geophysical Research: Solid Earth Ahmed and Lebedev (2019a) also observed grain crushing in sand during uniaxial loading in excess of 25 MPa, evident in digital microimages.…”
Section: 1029/2019jb017981mentioning
confidence: 90%
See 1 more Smart Citation
“…Journal of Geophysical Research: Solid Earth Ahmed and Lebedev (2019a) also observed grain crushing in sand during uniaxial loading in excess of 25 MPa, evident in digital microimages.…”
Section: 1029/2019jb017981mentioning
confidence: 90%
“…The most recent dry‐sand laboratory and analytical results are due to (a) Madadi et al (), where V p and V s are reported in several intact and crushed natural and artificial sand samples; (b) Ahmed and Lebedev (), where the authors analyze the effects of particle sorting and their shape on the elastic‐wave velocities and their ratio during uniaxial compaction of the samples; and (c) Ahmed and Lebedev (), where digital 3‐D images of sand are used to quantify the coordination number and grain‐to‐grain contact area as a function of sorting and grain roundness.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting these experiments on dry samples is challenging due to the very low acoustic impedance of a dry particulate system. Still, a number of publications offer these data for sand and glass beads, including Wyllie et al (), Domenico (), Murphy (), Yin (), Spencer et al (), Bhuiyan and Holt (), Madadi et al (), Ahmed and Lebedev ( and ), and Muqtadir et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Conducting these experiments on dry samples is challenging due to the very low acoustic impedance of a dry particulate system. Still, a number of publications offer these data for sand and glass beads, including Wyllie et al (1956), Domenico (1977), Murphy (1982), Yin (1992), Spencer et al (2004), Bhuiyan and Holt (2016), Madadi et al (2018), Lebedev (2019a and2019b), and Muqtadir et al (2019). Holt et al (2008) present experimental data on well-sorted spherical glass beads in the stress range between 1 and 15 MPa.…”
Section: Introductionmentioning
confidence: 99%